Micropropagation of Stevia rebaudiana Bertoni plants from ex vitro explan - Dionys González-Hernández; Elizabeth Kairuz Hernández-Díaz; Alina Capote; Anabel Pérez; Leonardo Rivero; Borys Chong-Pérez; Naivy Pérez-Alonso (Biotecnología Vegetal, 2019)
Stevia rebaudiana Bertoni is a species recognized worldwide for its medicinal properties. The objective of this work was to micropropagate Stevia plants from ex vitro explants. Shoots of plants of this specie growing at greenhouse were selected. In the in vitro establishment, the effect of disinfection time and the concentration of sodium hypochlorite on the survival of the explant were evaluated. The established explants were transferred to the multiplication culture medium, where the effect of the growth regulators (6-benzylaminopurine and indoleacetic acid) and the number of subcultures on the multiplication coefficient were determined. Then, the response of the plants in the acclimatization phase was evaluated, in comparison with plants propagated by cutting. Sodium hypochlorite at 1% allowed the disinfection of the explants with a survival of 94.5%, regardless of the time. The growth regulators did not modify the multiplication coefficient with subcultures every 15 days. It is possible to use different combinations of substrate based on zeolite and compost during the acclimatization of micropropagated plants. These developed a greater number of leaves and height than those propagated by cutting.